2014
DOI: 10.2478/s13536-013-0180-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two different methods for formation of the beta phase in nanocomposites based on vinylidene fluoride-hexafluoropropylene copolymer

Abstract: Nanocomposite materials based on vinylidene fluoride-hexafluoropropylene copolymer and organically modified montmorillonite Cloisite ® 15A were prepared by two different methods: melt mixing and co-precipitation. The changes taking place in crystalline structure, tensile strength, thermal behavior and the formation of piezoelectric β -phase as a result of the polymer system dissolution in dimethyl sulfoxide were studied. The technological specificity of each method has certain effect on the properties of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The asymmetrical and symmetrical stretching vibrations of CF 2 are present at 1179 and 1282 cm −1 [22]. Meanwhile, the peak for β-phase of PVDF-HFP appears at 873 cm −1 [32,33]. In general, these are characteristic peaks of PVDF-HFP, and they are consistent with the results of the following XRD spectrum analysis.…”
Section: Resultssupporting
confidence: 78%
“…The asymmetrical and symmetrical stretching vibrations of CF 2 are present at 1179 and 1282 cm −1 [22]. Meanwhile, the peak for β-phase of PVDF-HFP appears at 873 cm −1 [32,33]. In general, these are characteristic peaks of PVDF-HFP, and they are consistent with the results of the following XRD spectrum analysis.…”
Section: Resultssupporting
confidence: 78%
“…The β phase of PVDF is thermodynamically meta-stable phase with all trans (TTTT) zigzag chain conformation. 7,27 PVDF exhibits ferroelectric property as its electric dipole due to C-F and C-H can be changed in the presence of external electric field, 17 which is confirmed by the ferroelectric hysteresis loop. The SS (Switching spectroscopy)-PFM studies performed in all the samples at various locations confirm the presence of ferroelectric hysteresis with switching characteristics.…”
Section: (B)) a Close Agreement Between The Experimental Findings And...mentioning
confidence: 82%
“…Since our interest is mainly on understanding the ferroelectric domains of pure PVDF with its semicrystalline nature we continued our studies with PVDF and not sticking to the methods known to enhance the β-phase. 1,27,29,30,31,32,33 From above characterization we can conclude that the PVDF films in consideration mainly consists of β-phase along with minor fraction of other γ phase. Fig.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Clay dispersion in the rubber matrix was well observed by scanning electron microscope. 44,45 From SEM results it has been clearly observed that for most of the specimens clay particles were uniformly intercalated in the matrix along with the presence of some white inclusions. This is due to the improper mixing of clay particles within the ethylene propylene diene elastomer matrix.…”
Section: Sem Examinationmentioning
confidence: 99%